Legal consciousness and intimate partner violence survivors' perceptions of protection order violations - Hefner, M. Kristen (Journal of family violence, 2022)
Civil protection orders are individualized orders that survivors of intimate partner abuse and violence can pursue in addition to or independently of criminal charges. The efficacy of protection orders is defined in various ways in existing literature. One way to understand the effectiveness of these orders is to determine the extent to which they are violated, the willingness of survivors to report violations, and the legal system’s (i.e., police, criminal court, and civil court) responses to survivors’ reports. Research exists on the extent to which protection orders are violated, the extent to which violations are reported, and factors affecting enforcement of the orders. However, research has yet to examine the perceptions and behaviors of survivors who do not report order violations. Drawing on in-depth qualitative interviews with women who sought civil protection orders against abusive male partners, this research uses a legal consciousness framework to examine survivors’ perceptions of order violations, their decision-making processes regarding whether to report violations, and barriers to reporting the violations. The interviews reveal that not all survivors perceive contact as an order violation and, for those who do, not all survivors report the violations. Specifically, obstacles to reporting were related to survivors’ perceptions of the violations and accessibility to and usefulness of the legal system. Policy implications for both the civil and criminal justice systems to create more victim-centered and trauma-informed responses to survivors who experience protection order violations are discussed.